Experimental study of peripheral-blood pro-surfactant protein B for screening non-small cell lung cancer - He,Yong (2017)
Abstract Purpose: To evaluate the possibility of using peripheral-blood presurfactant protein B (Pro-SFTPB) for screening non-small cell lung cancer (NSCLC). Methods: A total of 873 healthy volunteers and 165 lung cancer patients hospitalized in the Fifth People’s Hospital of Dalian were tested Pro-SFTPB once every half year from January 2014 to September 2015. The healthy volunteers were also conducted spiral computed tomography (CT) examination once every year. The data were then com-pared and statistically analyzed. Results: The positive expression rate of Pro-SFTPB in NSCLC was significantly higher than that in healthy volunteers, and significantly higher in lung adenocarcinoma than in squamous cell carcinoma; additionally, the expression rate was increased with the in-crease of smoking index, and the intergroup differences showed statistical signifi-cance (p≤0.05). The positive rate of newly diagnosed lung cancer was 29.55%, higher than healthy volunteers (22.34%), but there was no significant difference (p>0.05). Conclusion: Pro-SFTPB is over expressed in non-small cell lung cancer, especially in lung adeno-carcinoma, but it can’t be used as a clinical screening tool for lung cancer.